Peran OJK, BI, dan DSN-MUI dalam Pengembangan Keuangan Syariah (Intregasi Regulasi dan Fatwa) - Rofiqy Nurus Sanusi; Amin Wahyudi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The Islamic finance industry in Indonesia has experienced significant growth and has the potential to become one of the global centers of Islamic finance. This development requires strong synergy between financial regulators and sharia authorities to ensure that the financial system operates in compliance with regulations while simultaneously adhering to sharia principles. This article aims to analyze the roles of the Financial Services Authority (OJK) and Bank Indonesia (BI) in regulating and supervising the Islamic financial system, as well as the role of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in issuing fatwas as sharia guidelines. Using a qualitative approach based on a literature review, the study finds that the integration of regulations and fatwas is the key to building a healthy, stable, and sustainable Islamic finance ecosystem. OJK and BI play roles in formulating adaptive regulations, while DSN-MUI ensures compliance with sharia principles through fatwas and the supervision of Sharia Supervisory Boards (SSB). This synergy has led to increased public trust, strengthened international competitiveness, and the emergence of innovative Islamic financial products, including Islamic fintech and green sukuk. The article concludes that collaboration among OJK, BI, and DSN-MUI needs to be continuously strengthened to respond to the dynamics of globalization and digitalization, thereby enabling Indonesia to reinforce its position in the international Islamic finance industry.